(untitled) (Research, Society and Development, 2021)
The objective of this study was to determine the chemical constituents of extruded sorghum flour (ESF) of genotype BRS 305 using mass spectrometry with paper spray ionization (PS/MS), a method that presents high precision, sensitivity and has low operating cost. Methanolextracts were prepared from the extruded sorghum flour sample and subsequently evaluated in positive and negative ionization modes. In the negative mode of ionization it was possible to identify 21 compounds, comprising the classes of flavonoids (48.0%), phenylpropanoids (28.0%), organic acids (9.0%), condensed tannins, fatty acids and carbohydrates (5.0% each). Additionally in the positive ionization mode, it was possible to identify 9 compounds, belonging to the classes of flavonoids (34.0%), carbohydrates (22.0%), amino acids (22.0%), fatty acids and terpenoids (11.0% each). The mass spectrometry by paper spray proved to be an efficient technique for fast finger prints of the (ESF) sample evaluated, identifying a total of thirty chemical compounds, reinforcing the nutritional and bioactive properties attributed to some sorb genotypes such as BRS 305.